Concurrent systems and time synchronization. Issue 4 (19th May 2018) - Burgin, Mark; Grathoff, Annette
Abstract: In the majority of scientific fields, system dynamics is described assuming existence of unique time for the whole system. However, it is established theoretically, for example, in relativity theory or in the system theory of time, and validated experimentally that there are different times and time scales in a variety of real systems – physical, chemical, biological, social, etc. In spite of this, there are no wide-ranging scientific approaches to exploration of such systems. Therefore, the goal of this paper is to study systems with this property. We call them concurrent systems because processes in them can go, events can happen and actions can be performed in different time scales. The problem of time synchronization is specifically explored.